The Contribution of Demoralization to End of Life Decisionmaking - Kissane, David W. (The Hastings Center report, 2004)
Some psychiatrists believe that “demoralization syndrome” is a diagnosable cognitive disorder characterized in its extreme form by morbid existential distress. If they are right, then it should be an important part of our thinking about end of life decisionmaking. A demoralized patient would be unable to think reliably about the remainder of her life, and therefore incompetent to decide to commit physician-assisted suicide.